Analisis Efektivitas Pajak Daerah Dan Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah - Rismania Br Barus; Alistraja Dison Silalahi; Arie Pratania Putri (STIE AMKOP, 2023)
This research aims to find out how the effectiveness of local taxes and the contribution of local taxes to regional original income in the province of North Sumatra. This study uses a qualitative descriptive research method. In this study, the government of North Sumatra Province became the subject of this research. The object of this study is the target and realization of local taxes and local revenue of North Sumatra Province. This research uses secondary data, the method used for data collection is the documentation method, namely by recording and examining archives and documents in agencies related to research both in the form of information, financial data, and others. The results show that on average the level of effectiveness of local taxes in the province of North Sumatra is 82%, which is quite effective. The results show that the ability of local governments to realize local tax revenues based on predetermined targets is well implemented, with the hope that there will be a reduction in dependence on finance from the central government. On average, the level of contribution of local taxes to the local revenue of North Sumatra Province, which is 53%, is very good. Keyword: Local Tax, Regional Original Revenue, Effectiveness, Contribution